The acceptance of employees toward social networking technology at DEMC Specialist Hospital Shah Alam / Zurulain Ahmad - Ahmad, Zurulain (2015)
The recent advent of social networking has changed the way people communicate and connect with each other. As a result, several studies have been conducted on social networking, but they rarely touched on the user acceptance of social networking by employees. This study is attempts to explaining the user acceptance of social networking by proposing a research model for the acceptance of social networking by employees, based on the technology acceptance model (TAM). I do this by examining the extent to which the perceptions of 80 employees about the usefulness, enjoyment, and ease of use of social networking affect the intention to adopt the use of social networking.